(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The experiment was carried out at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Jessore to evaluate the performance of different varieties of hybrid maize under intercropping systems with groundnut in rabi seasons to find out the suitable intercropping system in increasing crop productivity and profitability of consecutive two years (2004 and 2005). Four sole crops of hybrid maize varieties (BHM-1, BHM-3, Pacific-11 and Pacific-984), one sole crop of groundnut (var. Jhingabadam) and eight intercropping systems of maize + groundnut under two planting methods viz., normal and paired row made 13 treatments were used. Treatments were arranged in a randomized complete block design with four replications. Among the intercropped treatments, four rows groundnut in between paired rows of hybrid maize var. Pacific-11 showed higher maize equivalent yield (13.56 t/ha in 2003-04 and 15.34 t/ha in 2004-05), groundnut equivalent yield (4.34 t/ha in 2003-04 and 4.91 t/ha in 2004-05), land equivalent ratio (1.54 in 2003-04 and 1.66 in 2004-05) as compared to other treatments. Key Words: Hybrid maize varieties; intercropping systems; groundnut. DOI: 10.3329/bjar.v34i4.5835 Bangladesh J. Agril. Res. 34(4) : 585-595, December 2009